Professionalism for intern blood transfusion biomedical technologists: an exploration of perceptions and potential teaching strategies - Rambiritch, Vanitha (Stellenbosch : Stellenbosch University, 2016)
Thesis (MPhil)--Stellenbosch University, 2016.